2019
DOI: 10.3389/fphar.2019.01411
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Effects of Panax ginseng Berry Polysaccharides via Activation of Immune-Related Cells

Abstract: Panax ginseng has long been used as natural medicine and health food all over the world. Cancer is a major cause of death worldwide and its prognosis likely depends on the immune system during tumor treatment. In this study, ginseng berry polysaccharides were evaluated for their immunostimulant and anti-cancer effects. Ginseng berry polysaccharide portion (GBPP) was used to investigate its effects on anti-complementary activity, peritoneal macrophage activation, and natural killer (NK) cell cytotoxicity. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 61 publications
1
34
0
Order By: Relevance
“…Therefore, numerous studies have been conducted to identify safer and more effective anti-asthma drugs [ 4 , 8 , 13 , 17 , 18 , 28 ]. Korean Red Ginseng is known to affect various aspects of physiology, such as immunity [ 25 ], circulation [ 26 ], and inflammation [ 27 ], and diseases, such as allergy [ 28 ], cancer [ 29 ], metabolic diseases [ 30 ], and neurodegenerative diseases [ 31 ]. In asthma patient severe airway blockage was observed and this symptom was caused by airway remodeling which is related with epithelial cell and goblet cell hyperplasia, mucous hypersecretion by goblet cells, etc [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, numerous studies have been conducted to identify safer and more effective anti-asthma drugs [ 4 , 8 , 13 , 17 , 18 , 28 ]. Korean Red Ginseng is known to affect various aspects of physiology, such as immunity [ 25 ], circulation [ 26 ], and inflammation [ 27 ], and diseases, such as allergy [ 28 ], cancer [ 29 ], metabolic diseases [ 30 ], and neurodegenerative diseases [ 31 ]. In asthma patient severe airway blockage was observed and this symptom was caused by airway remodeling which is related with epithelial cell and goblet cell hyperplasia, mucous hypersecretion by goblet cells, etc [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Korean Red Ginseng ( Panax ginseng Meyer) is one of important traditional medicines [ 24 ], and recent studies reported effects of ginseng compounds on physiological functions, including immunity [ 25 ], circulation [ 26 ], and inflammation [ 27 ], and diseases, such as allergies [ 28 ], cancer [ 29 ], metabolic diseases [ 30 ], and neurodegenerative diseases [ 31 ]. In the present study, therapeutic effects and mechanisms of action of Korean Red Ginseng were assessed using an ovalbumin (OVA)-induced asthma model.…”
Section: Introductionmentioning
confidence: 99%
“…Heparin has been used in clinics since 1935, mainly due to its anticoagulant activity [ 17 ]. Considering that heparin may be a ligand for stimulatory receptors on NK cells (NKp30, NKp44 and NKp46), and it is currently used for NK cell product manufacturing purposes [ 36 ], in addition to other polysaccharides with potential to stimulate NK cells [ 40 , 41 , 42 ], we evaluated the capacity of heparin to stimulate and increase killing capacity of NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have examined their structure and pharmacological activities [ 11 ]. RG-I and RG-II isolated from natural products have been reported to possess pharmacological activities such as complement activating activity, stimulation of macrophages [ 14 ], bone marrow cell proliferation mediated by intestinal immune system [ 15 ], natural killer (NK) cell cytotoxicity, including cytolytic activity against cancer cell lines [ 16 , 17 ], and anti-metastatic effects in vivo [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%